Hyperfine structure of Sc@C82 from ESR and DFT - Morley, G; Herbert, B; Lee, S; Porfyrakis, K; Dennis, T; Nguyen-Manh, D; Scipioni, R; Van Tol, J; Horsfield, A; Ardavan, A; Pettifor, D; Green, J; et al. (2005)
The electron spin g- and hyperfine tensors of the endohedral metallofullerene Sc@C82 are anisotropic. Using electron spin resonance (ESR) and density functional theory (DFT), we can relate their principal axes to the coordinate frame of the molecule, finding that the g-tensor is not axially symmetric. The Sc bond with the cage is partly covalent and partly ionic. Most of the electron spin density is distributed around the carbon cage, but 5% is associated with the scandium dyz orbital, and this drives the observed anisotropy. © 2005 IOP Publishing Ltd.